2017
DOI: 10.1186/s12939-017-0605-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying inequitable healthcare in older people: systematic review of current research practice

Abstract: BackgroundThere is growing consensus on the importance of identifying age-related inequities in the receipt of public health and healthcare interventions, but concerns regarding conceptual and methodological rigour in this area of research. Establishing age inequity in receipt requires evidence of a difference that is not an artefact of poor measurement of need or receipt; is not warranted on the grounds of patient preference or clinical safety; and is judged to be unfair.MethodA systematic, thematic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…The study by Araújo et al (2014) evaluated the quality of PHC in FHS in a city in Northeastern Brazil from the perspective of the elderly and identified that the units studied had a high degree of orientation for the component Use of the First Contact Access attribute and low degree for the Accessibility component of this same attribute, corroborating the findings of this study. Salway et al (2017) verified in their study that the elderly access is unequal. Higher income and education were associated with the use and access to consultations (ZANESCO et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…The study by Araújo et al (2014) evaluated the quality of PHC in FHS in a city in Northeastern Brazil from the perspective of the elderly and identified that the units studied had a high degree of orientation for the component Use of the First Contact Access attribute and low degree for the Accessibility component of this same attribute, corroborating the findings of this study. Salway et al (2017) verified in their study that the elderly access is unequal. Higher income and education were associated with the use and access to consultations (ZANESCO et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…However, since language proficiency and other variables such as nursing staffing ratio and communication modality were not available, this relationship cannot be established. The relationship between increasing age and longer NPO duration may also be a manifestation of established disparities described in the care of the elderly ( 21 , 22 ), though the absolute differences in times across the age spectrum are still relatively small. The inverse relationship with hospital occupancy may reflect a heightened urgency to get patients treated sooner to reduce a backlog of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Há poucos estudos que exploram o acesso dos longevos aos serviços de saúde e que, em muitos casos, esse acesso é desigual 19 . Maior renda e escolaridade estiveram associadas à utilização e acesso a consultas 20 .…”
Section: Discussionunclassified